PENGARUH STRATEGI DISKON TERHADAP MINAT BELI MAHASISWA PADA PLATFORM E-COMMERCE - Tri Desi Lestari; Muhammad Nurhadi N (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
The rapid growth of e-commerce platforms has intensified competition, prompting businesses to utilize various promotional strategies to attract consumers. Among these strategies, discounts are one of the most effective forms of promotion for boosting purchasing interest, especially among students who are known to be price sensitive. This study aims to analyze the influence of discount strategies on students' purchasing interest in the Management Study Program at STIE Amkop Makassar who made purchases through e-commerce platforms. The research used a quantitative approach by distributing questionnaires to 299 respondents selected from the population of active students in the even semester of 2024/2025, based on the Pangkalan Data Pendidikan Tinggi. Data analysis includes validity and reliability testing, as well as simple linear regression to examine the influence of independent variables on purchase interest. The research findings indicate that discount strategies have a positive and significant impact on students' purchase intention, confirming that the perceived economic benefits and value of discounts play a crucial role in shaping consumer behavior in the digital environment. This research contributes to the digital consumer behavior literature and emphasizes the importance of optimizing discount programs in increasing the engagement and interest of student consumers. Practical implications suggest that e-commerce platforms should strengthen the design of discount programs to be more relevant and appealing. Further research is suggested to include additional variables such as trust, service quality, and digital promotion strategies to produce a more comprehensive analysis.